Consumer Attitude Analysis With Respect to Reading of Newspapers & Magazines (With Reference to Nagapattinam District, Tamil Nadu) - Chandrasekar, K. (Indian Journal of Marketing, 2006)
Reading books and journals has become a part and parcel of every day life of human beings. The reading habits help the people to make use of the leisure time usefully. Newspapers are brought largely for their news value. As such they are most appropriate for announcing new products and the development of existing products. Because of the frequency of publication they are also well suited to "Opportunity Market".Journalism includes the writing and editing of newspapers and periodicals. The word "Journalism" is derived from "Journal" which means a daily register or a diary or a book containing each day's business or transactions. The word Journal also connects a newspaper published every day or even less often or a magazine.